A logistical approach to facilitate the treatment control process for hospital - Phuong, Nguyen Huynh Luu (Journal of Transportation Science and Technology, 2022)
The treatment control process in hospitals in Vietnam is still ineffective due to paper-based documents, poor information flow between related parties, incorrect data, inefficient working methods, and so on… In medical service, medication errors such as prescribing, omission, wrong time, administration error, compliance error… are very serious problems due to the negative effects on patient’s health. Thus, accuracy is a must in this industry. These problems are not only apparent in Vietnam but also obvious on over the world. This article needs to show some reasons and suggest a model to solve the problem based on the logistics angle view. Some knowledge about the Logistics information system and Logistics service outsourcing model is used to facilitate the treatment control process for hospitals. This article aims to optimize the information flow, operations to increase the timeliness, accuracy, decrease the operating cost, and improve safety.
Keywords: Barcode; hospital; Logistics; logistics information system; outsourcing; treatment control